Odpowiedzi

Najlepsza Odpowiedź!
2010-01-14T16:05:16+01:00
X + 3x =4x

3/4x + x =23/4x

5x + 2x = 7x

3x + 0,6x =3,6x

x - 1/2x =1/2x

x - 1/3x =2/3x

5x - x =4x

3x - 0,5x = 2,5x

-5x+x = -4x

-2x-3x = -5x

5x-(-x) = 6x

-10x-(-x) = -9x

x/2 - x = x/3 (nie jestem pewna)

Mam nadzieje że pomogłam :*
7 4 7
2010-01-14T16:06:02+01:00
4x
1 i 3/4x
7x
3,6x
1/2x
2/3x
4x
2,5x
-4x
-5x
6x
-9x

3 5 3
2010-01-14T16:08:41+01:00
4xkwadrat
1/3xkwadrat
7xkwadrat
3,6xkwadrat
1/2xkwadrat
1/3xkwadrat
4xkwadrat
2,5xkwadrat
-4xkwadrat
-5xkwadrat
4xkwadrat
-11xkwadrat
2 5 2